THE EFFECT OF CROSS-BORDER MERGERS AND ACQUISITIONS ON INDIAN FIRMS’ PERFORMANCE - Nguyen, Thi Huyen Trang (2012)
The purpose of this paper is to examine the effect of cross-border M&As on Indian firms’ performance. It also mentions the literature review about M&As background and existing findings and methodology. In order to evaluate the effect, this paper uses the dataset including 151,141 observations of Indian companies in the period 1988-2009. The accounting-based data methodology is used in this research. The determinants for analyzing the effect of cross-border M&As are the effect of size of company, age, market share, leverage and M&As status on PBDIT (profit before depreciation, interest and tax) and PBIT (profit before interest and tax). All the results show that the most of factors bring the positive impacts on profitability except leverage. The results also demonstrate that companies which are involved in cross-border M&As have a higher profitability than non-cross-border M&As company. Although there have some limitations of this project in sample size of observations and methodology, this research still contribute some helpful implications about the effect of cross-border M&As in Indian companies. That is also a background step to carry out this project in the future to improve the above limitations and expand in a larger size and combined methodology.